Jumping performance in elite female volleyball players relative to playing positions: A practical multidimensional assessment modeübersetzter Titel (DE) - Dopsaj, M.; Copic, N.; Nesic, G.; Sikimic, M. (Serbian Journal of Sports Sciences, 2012)
The aim of this study was to define a practical multidimensional model for assessing the general level of jumping performance relative to playing positions in elite female volleyball players, successful competitors at top international levels. The present study undertook the task to determine whether there were differences related to jumping performance in elite female volleyball players in relation to their playing position in the game (Correction, Receiver, Blocker, Setter and Libero). A set of 7 variables was used to assess the jumping levels, with 6 variables covering the space of vertical jumping while 1 variable covered horizontal jumping skills. Standardized field tests (Abalakov method and standing long jump) were used for all measurements. The data were processed by the multivariate statistical method. The results indicated that there were no general statistically significant differences between jumping skill levels in elite female volleyball players relative to playing positions (Wilks' Lambda Value - 0.135, F relation - 1.281, p = 0.204) measured by the method applied. According to the descriptive results for the general jumping score (JUMPscore), the elite female volleyball players at Receiver positions had the highest jumping scores with 66.58 ± 9.18 score points, while Setters scored the lowest, 54.52 ± 10.34.